Ожиріння та метаболічний синдром у дітей - Зелінська, Н. Б. (Clinical Endocrinology and Endocrine Surgery, 2013)
The article presents the causes of obesity, its principles of diagnosis, current data of the role of obesity in the development of metabolic syndrome in children. Also it describes the components of the metabolic syndrome in children and adolescents, its criteria and treatment.